Preoperative systemic inflammatory response index predicts long-term outcomes in type B aortic dissection after endovascular repair - Zhao, Yufei; Hong, Xiang; Xie, Xinsheng; Guo, Daqiao; Chen, Bin; Fu, Weiguo; Wang, Lixin (Frontiers in Immunology, 2022)
Objectives Inflammation is a hallmark of the initial development and progression of aortic dissection. This study aimed to investigate the value of preoperative inflammatory biomarkers in predicting aorta-related adverse events (AAEs) after thoracic endovascular aortic repair (TEVAR) for type B aortic dissection. Methods We included all patients who underwent TEVAR for type B aortic dissection between November 2016 and November 2020 in this single-center, retrospective cohort study. Patients were divided into two groups: the AAEs group (n = 75) and the non-AAEs group (n = 126). Preoperative inflammatory biomarkers were recorded, including neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), systemic immune inflammation index (SII), and systemic inflammatory response index (SIRI). Patients were followed-up for the development of AAEs. Prediction accuracy of inflammatory biomarkers for AAEs were evaluated using the area under the receiver operating characteristic curves. Results This study included 201 patients, of whom 80.0% were men, with a mean age of 59.1 ± 12.5 years. A total of 75 patients developed AAEs after TEVAR. The AUCs of NLR, MLR, PLR, SII, and SIRI for AAEs were.746,.782,.534,.625 and.807, respectively. Age and SIRI were independent risk factors for the AAEs after TEVAR (HR 3.264, p <.001; HR 4.281, p <.001, respectively). Survival analysis revealed significantly lower AAE-free status in patients with preoperative SIRI > = 4 (p <.001). Conclusion Increased preoperative SIRI and age are independent risk factors for AAEs after TEVAR in type B aortic dissection.